2019
DOI: 10.1158/2326-6066.cir-18-0709
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Immune-Checkpoint B7-H4 and Lysine Demethylase 5B in Esophageal Squamous Cell Carcinoma Confers Protective Immunity against P. gingivalis Infection

Abstract: Pathogens are capable of hijacking immune defense mechanisms, thereby creating a tolerogenic environment for hypermutated malignant cells that arise within the site of infection. Immune checkpoint-oriented immunotherapies have shown considerable promise. Equally important, the epigenetic reprogramming of an immune-evasive phenotype that activates the immune system in a synergistic manner can improve immunotherapy outcomes. These advances have led to combinations of epigenetic-and immune-based therapeutics. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
(48 reference statements)
0
29
0
Order By: Relevance
“…Carcinogen metabolism by P. gingivalis may therefore be a possible mechanism [ 84 ]. Further, Yuan et al highlighted the ability of P. gingivalis to evade immune surveillance, and they determined that the blockade of immune-checkpoint B7-H4 and lysine demethylase 5b in ESCC conferred resistance against P. gingivalis infection and tumor challenge, proposing them as potential therapeutic targets for controlling P. gingivalis infection and its associated neoplasia [ 86 ]. Furthermore, P. gingivalis can enhance ESCC cell proliferation and metastasis by triggering the NF-ĪŗB signaling pathway [ 87 ] or via the miR-194/GRHL3/PTEN/Akt axis [ 88 ].…”
Section: Oncologymentioning
confidence: 99%
“…Carcinogen metabolism by P. gingivalis may therefore be a possible mechanism [ 84 ]. Further, Yuan et al highlighted the ability of P. gingivalis to evade immune surveillance, and they determined that the blockade of immune-checkpoint B7-H4 and lysine demethylase 5b in ESCC conferred resistance against P. gingivalis infection and tumor challenge, proposing them as potential therapeutic targets for controlling P. gingivalis infection and its associated neoplasia [ 86 ]. Furthermore, P. gingivalis can enhance ESCC cell proliferation and metastasis by triggering the NF-ĪŗB signaling pathway [ 87 ] or via the miR-194/GRHL3/PTEN/Akt axis [ 88 ].…”
Section: Oncologymentioning
confidence: 99%
“…Currently, ESCC patients are mainly treated using surgical approaches, as well as by radiotherapy or chemotherapy, depending on the pathological results. Although chemotherapeutic drugs improve outcomes of esophageal carcinoma patients to a certain extent, the prognosis of ESCC remains dismal (2). Although several antitumor drugs such as paclitaxel (6), vincristine (8) and colchicine (31), are available for clinical application, they have limited efficacy in killing tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal carcinoma (EC), that occurs in the squamous or glandular epithelium of the esophagus, represents the predominant type of gastrointestinal tumors (1,2). EC is further divided into esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…93,118 A recent study suggested that blockade of immune checkpoints could effectively diminish the carcinogenic influence of P. gingivalis in ESCC. 119 F. nucleatum can also induce high-level expression of some pro-inflammatory cytokines including IL-6 and IL-8, 31 which are key promoters in inflammation-related diseases.…”
Section: Excessive Inflammatory Reaction In Response To Microbiotamentioning
confidence: 99%